Senam Lansia Untuk Meningkatkan Kualitas Hidup Lansia Di Dusun II Desa Sumber Sari Kec Kebawetan Kab Kepahiang - Eka Puspitasari; Indah Jannatin; Ena Purnama Putri; Pretty Nove Lisa; Ecah Belah; Imelda Lestari; Nimas Ayu Lestari Nurjanah (Utami Publisher, 2025)
The elderly are a vulnerable group that experiences a decline in physical function and quality of life, requiring easy and safe promotional interventions such as exercise for the elderly. This activity aims to improve the quality of life of the elderly and increase their knowledge in Hamlet 2, Sumber Sari Village. This program was held on Thursday, November 27, 2025, in the residential area of Hamlet 2, Kabawetan Subdistrict, targeting the elderly. The activity method used demonstrations of exercise for the elderly as a hands-on approach and hypertension screening for initial blood pressure checks. There were 20 elderly people who participated in this activity. The results of the activity showed that all participants were able to follow the exercise movements enthusiastically, and from the screening results, it was found that some participants had blood pressure above the normal limit, so they were given further education on healthy lifestyles. It was concluded that the demonstration method was effective in increasing the physical participation of the elderly and that elderly exercise had the potential to improve quality of life if done regularly, while hypertension screening was important for the prevention of health complications. It is recommended that senior citizen exercise be continued periodically through village health cadres, accompanied by routine blood pressure monitoring. Recommendations for health centers and village officials include strengthening community-based senior citizen health programs, providing exercise assistance, and improving follow-up for senior citizens with hypertension screening results.